The Enforcement of Environmental Criminal Law in Customary Law Community - Purwani, Sagung Putri M.E. (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 11 No 1 (2022)DO - 10.24843/JMHU.2022.v11.i01.p13, 2022)
The purpose of this paper was to examine and analyze the regulation of criminal sanctions in environmental crimes by customary law community, and analyze customary law community policies in the settlement of environmental crimes. This paper was normative research with a statutory and conceptual approach. The results of the study indicated that Based on all the abovementioned, it can be concluded that the regulation of Environmental Criminal Enforcement by Customary Law Community has been regulated in the provisions of environmental laws and regulations, namely Law No. 32 of 2009 concerning Environmental Protection and Management, Law No. 41 of 1999 concerning Forestry, and Regulation of the Minister of Environment and Forestry Number 32 of 2015 concerning Forests. Further, there are also environmental criminal laws which are regulated in other sectoral laws relating to the environment and natural resources. Regarding the Settlement of Environmental Crimes by Customary law community, it is done through efforts to arrange Deliberations and Restorations in the balance of nature and the environment that were previously damaged and polluted by customary law community. Thus, there is a need for recognition and management of customary forests that must be carried out professionally and sustainably based on local wisdom. Hence, it is expected to be able to improve equitable welfare.